2001
DOI: 10.1111/1475-4983.00182
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb of a giant terrestrial bird from the upper Eocene, Fayum, Egypt

Abstract: ABSTRACT. Eremopezus eocaenus Andrews, 1904 is a giant groundbird from upper Eocene deposits of the Fayum, Egypt, which has hitherto been known from non-diagnostic fragmentary material. New fossils collected from quarry L-41 of the Jebel Qatrani Formation include two well-preserved distal tarsometatarsi and an associated whole tarsometatarsus and distal tibiotarsus that allow a more precise evaluation of the phylogenetic position and tarsal function of Eremopezus. Unlike most ratites, the distal tarsometatarsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Based on the living relatives of the Jebel Qatrani teleosts, the palaeoenvironment represented by these deposits probably included open waters and deep rivers, along with abundant vegetation. The teleost ®shes from the Jebel Qatrani indicate the same type of environment as has previously been proposed based on the bird assemblage (Rasmussen et al 1987). The fossil birds are related to modern forms that prefer waters with slow currents and lentic conditions with emergent aquatic vegetation, swampy areas, or extensive over-bank areas (Rasmussen et al 1987).…”
Section: A S S O C I a T E D N O N -T E L E O S T F I S H E Smentioning
confidence: 65%
See 3 more Smart Citations
“…Based on the living relatives of the Jebel Qatrani teleosts, the palaeoenvironment represented by these deposits probably included open waters and deep rivers, along with abundant vegetation. The teleost ®shes from the Jebel Qatrani indicate the same type of environment as has previously been proposed based on the bird assemblage (Rasmussen et al 1987). The fossil birds are related to modern forms that prefer waters with slow currents and lentic conditions with emergent aquatic vegetation, swampy areas, or extensive over-bank areas (Rasmussen et al 1987).…”
Section: A S S O C I a T E D N O N -T E L E O S T F I S H E Smentioning
confidence: 65%
“…The teleost ®shes from the Jebel Qatrani indicate the same type of environment as has previously been proposed based on the bird assemblage (Rasmussen et al 1987). The fossil birds are related to modern forms that prefer waters with slow currents and lentic conditions with emergent aquatic vegetation, swampy areas, or extensive over-bank areas (Rasmussen et al 1987). Wing and Tiffney (1982) have suggested that in Oligocene times, the Fayum contained a shallow swampy river, or series of rivers, overgrown in places with papyrus, reeds and¯oating vegetation such as Salvinia and water lilies.…”
Section: A S S O C I a T E D N O N -T E L E O S T F I S H E Smentioning
confidence: 75%
See 2 more Smart Citations
“…However, among the sub‐fossil birds that went extinct very recently, Aepyornithidae are considered to be graviportal (Amadon ; Rasmussen et al . ; Murray and Vickers‐Rich ) and can therefore serve for comparison.…”
Section: Abbreviationsmentioning
confidence: 99%